Analysis of the Effect of Earnings Management on Audit Service Fees in Five ASEAN-5 Countries (Jurnal Dinamika Akuntansi, 2020)
This research aims to provide empirical evidence about the effect of earnings management on the audit fee spent by listed firms in ASEAN-5. This research was conducted using regression analysis with sample of 5.396 firm year listed in ASEAN countries, such as Indonesia, Malaysia, Philippines, Singapore, and Thailand from 2010-2014. The result of this study indicates that earnings management will increase audit fee. It is due to earnings management increase inherent risk faced by auditor.